(untitled) (Journal of Shaheed Suhrawardy Medical College, 2018)
Background: Benign disorder of breast in female usually seen in reproductive period of life, is thought to be largely hormone induced and there is a dramatic fall in the incidence after menopause due to cessation of ovarian stimulation. Objectives: To find out the relationship between different types of benign breast disease and hormones acting on breast mainly oestrogen, testesteron and prolactin. Methodology: This is a prospective observational study conducted in the department of surgery, Shaheed Suhrawardy Medical College Hospital. Total 150 female patients of reproductive age were included in the study. Serum levels of oestrogen, testosterone and prolactin were done in all patients. Other relevant radiological and cytological investigations were done accordingly where indicated. Results: Mean age of the study subjects were 28 ±8.46 years. Among the study subjects 64 (42.7%) patients used hormonal contraception, on the other hand 86 patients (57.3%) did not used hormonal contraceptive. 68 (45.3%) patients were non parous, 29( 19.3%) were primi parous and 53 ( 35.3%) were multiparous. 87 (58%) had positive history of breast feeding, 63 (42%) patients did not breast fed their babies. Fibrocystic disease was most common diagnosis among study group followed by fibroadenoma. 96 (64%) patients had fibrocystic disease followed by 38 (25.3%) had fibroadenoma. Mean oestrogen, testosterone and prolactin level was 71.16± 57.63 pg/ml, 0.59 ± 0.42 nmol/L and 22.61 ± 16.65 ng/ml respectively. Conclusion: With this small sample size it is difficult to conclude regarding relation between oestrogen, testosterone, prolactin and benign breast disease. But this study can be used as a base line document regarding benign breast disease, hormone profile, type, distribution and frequency of benign breast disease. J Shaheed Suhrawardy Med Coll, December 2016, Vol.8(2); 54-57